American football uniforms elicit thermoregulatory failure during a heat tolerance test. Issue 3 (3rd July 2021) - Launstein, Ethan D.; Miller, Kevin C.; O'Connor, Paul; Adams, William M.; Abrego, Megan L.
ABSTRACT: The Israeli Defense Force's heat tolerance test (HTT) helps clinicians make return-to-activity decisions following exertional heatstroke. Participants fail the test and are "heat intolerant" if rectal temperature (TREC ) or heart rate (HR) exceed 38.5°C or 150 bpm, respectively. Ideally, tests assessing athlete heat tolerance would incorporate sport-specific factors (e.g., protective equipment). Because few clothes are worn during a HTT, its ability to assess American football players' heat tolerance may be limited. We hypothesized wearing an American football uniform (PADS) during a HTT would lead to more classifications of heat intolerance. In this randomized, counterbalanced, crossover study, 10 men without recent exertional heat illness (age: 23 ± 3 y; mass: 78.5 ± 10.3 kg; height: 179.6 ± 7.6 cm) completed a standard HTT (CONTROL) or an HTT with PADS donned. TREC and HR were monitored continuously for 2 hours or until TREC reached 39.5°C. We noted when HTT failure criteria occurred. All participants failed the HTT in PADS (n = 2, TREC >38.5°C; n = 8, HR >150 bpm); 5 failed in CONTROL (n = 1, TREC >38.5°C; n = 4, HR >150 bpm). Participants completed more of the HTT before failure in CONTROL than PADS (61.7 ± 23.5 min vs. 43.4 ± 14.2 min; t9 = 1.9, P =.04). The HTT cannot be made more sport-specific by simply donning PADS because PADS impaired thermoregulatory ability and produced more false positive HTT results. Consequently, the HTT should not be the sole determinant of an American football players return-to-activity following heat illness. New methods of testing heat tolerance in American football players are needed since the existing HTT is not sport specific.ABBREVIATIONS: EHS: exertional heatstroke; HR: heart rate; HTT: The Israeli Defense Force's heat tolerance test; PADS: full American football uniform consisting of a helmet; shoulder, knee, thigh, hip and tailbone pads; a jersey top; undergarments; and half-length pants; PHT: probability of heat tolerance; RMANOVA: repeated measures analysis of variance; RPE: rating of perceived exertion; RTP: return to play; TCR: thermal-circulatory ratio; TREC: rectal temperature; VO2max : maximal oxygen consumption